The Prognostic Value of One-Year Changes in Biventricular Mechanics for Three-Year Survival in Patients with Precapillary Pulmonary Hypertension: A Cardiovascular Magnetic Resonance Feature Tracking Study - Padervinskienė, Lina; Ažukaitė, Joana; Hoppenot, Deimantė; Krivickienė, Aušra; Šimkus, Paulius; Nedzelskienė, Irena; Miliauskas, Skaidrius; Ereminienė, Eglė (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: The management of patients with pulmonary hypertension (PH) poses a considerable challenge. While baseline cardiac magnetic resonance imaging (cMRI) indices are recognized for survival prognosis in PH, the prognostic value of one-year changes in biventricular mechanics, especially as assessed using feature tracking (FT) technology, remains underexplored. This study aims to assess the predictive value of one-year change in cMRI-derived biventricular function and mechanics parameters, along with N-terminal pro-brain natriuretic peptide (NT-proBNP) levels and six-minute walking test (6MWT) results for three-year mortality in precapillary PH patients. Materials and Methods: In this retrospective study, 36 patients diagnosed with precapillary pulmonary hypertension (mPAP 55.0 [46.3–70.5] mmHg, pulmonary capillary wedge pressure 10.0 [6.0–11.0] mmHg) were included. Baseline and one-year follow-up cMRI assessments, clinical data, and NT-proBNP levels were analyzed. FT technology was utilized to assess biventricular strain parameters. Patients were categorized into survival and non-survival groups based on three-year outcomes. Statistical analyses, including univariate logistic regression and Cox regression, were performed to identify predictive parameters. Results: The observed three-year survival rate was 83.3%. Baseline right ventricle (RV) ejection fraction (EF) was significantly higher in the survival group compared to non-survivors (41.0 [33.75–47.25]% vs. 28.0 [23.5–36.3]%, p = 0.044), and values of ≤32.5% were linked to a 20-fold increase in mortality risk. RV septum longitudinal strain (LS) and RV global LS exhibited significant improvement over a one-year period in the survival group compared to the non-survival group (−1.2 [−6.4–1.6]% vs. 4.9 [1.5–6.7]%, p = 0.038 and −3.1 [−9.1–2.6]% vs. 4.5 [−2.1–8.5]%, p = 0.048, respectively). Declines in RV septum LS by ≥2.95% and in RV GLS by ≥3.60% were associated with a 25-fold and 8-fold increase in mortality risk, respectively. Conclusions: The decrease in right ventricular septal and global longitudinal strain over a one-year period demonstrates a significant predictive value and an association with an increased three-year mortality risk in patients with precapillary PH.